2009
DOI: 10.1248/bpb.32.1371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeic Acid on Tumor Necrosis Factor-Alpha-Induced Vascular Inflammation in Human Umbilical Vein Endothelial Cells

Abstract: Recruitment of specific leukocyte subpopulations at the site of inflammation requires a series of cell adhesion molecules (CAMs)-mediated interactions. The major CAMs, viz., intracellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and E-selectin are expressed on endothelium in response to various cytokines. Caffeic acid (CA), a natural phenolic compound from herbs and other sources, has been shown to prevent cardiovascular diseases. We investigated the effect of CA on the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 43 publications
2
45
0
Order By: Relevance
“…19) Our findings also demonstrated that CA reduced TNF-α-induced NF-κB activation in human keratinocytes. The findings suggested that CA might effectively modulate the transcriptional activity of NF-κB in cutaneous inflammatory responses, which is critical for the transcriptional regulation of many pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…19) Our findings also demonstrated that CA reduced TNF-α-induced NF-κB activation in human keratinocytes. The findings suggested that CA might effectively modulate the transcriptional activity of NF-κB in cutaneous inflammatory responses, which is critical for the transcriptional regulation of many pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 71%
“…Since CA was demonstrated to have an ability to reduce TNF-α-induced vascular inflammation by targeting pathways that result in the activation of the nuclear transcription factor NF-κB, 19) we further investigated whether CA treatment decreased the NF-κB activity in human keratinocytes. Keratinocyte cells were transiently transfected with pNF-κB-Luc reporter plasmid, stimulated with 10 ng/mL TNF-α in the presence or absence of CA, and then measured the luciferase acitivty, which served as an indicator of NF-κB activation.…”
Section: Effect Of Ca On Pro-inflammatory Mediators In Human Keratinomentioning
confidence: 99%
See 2 more Smart Citations
“…15 Several types of natural antioxidants, including flavonoids and polyphenolic compounds, inhibit adhesion molecule expression, and the adhesion of monocytes to endothelial cells, and are believed to suppress inflammation, transformation, proliferation, survival, invasion, and angiogenesis. 16,17 Chlorophylls (Chls), the most abundant green pigments found in plants, are important in photosynthesis. Chls are constituents of the diet, especially from green vegetables and fruits.…”
Section: Introduction Ementioning
confidence: 99%